2015
DOI: 10.5902/1980509820583
|View full text |Cite
|
Sign up to set email alerts
|

CRESCIMENTO, ACÚMULO DE NUTRIENTES E FENÓIS TOTAIS DE MUDAS DE CEDRO-AUSTRALIANO (<i>Toona ciliata</i>) INOCULADAS COM FUNGOS MICORRÍZICOS

Abstract: RESUMOO presente estudo teve por objetivo avaliar a produção de mudas de cedro-australiano quanto à capacidade de crescimento, nutrição e produção de fenóis totais inoculadas com fungos micorrízicos arbusculares (FMAs). Realizou-se experimento em casa de vegetação com três tratamentos compostos por Gigaspora margarita, Glomus clarum e Glomus etunicatum testados de forma isolada e quatro tratamentos compostos pela combinação destas espécies: Gigaspora margarita + Glomus clarum, Gigaspora margarita + Glomus etun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 2 publications
1
15
1
8
Order By: Relevance
“…Similar to our work, Caldeira et al (2012) found out that higher shoot heights were obtained for substrates with a higher proportion of biosolids, which, among the substrates tested in their work, were also the one with the highest concentration of N. The shoot heights obtained with a higher proportion of biosolids were similar to those observed for seedlings submitted to a nitrogen concentration of 2000 mg L -1 for 7 days and 4000 mg L -1 for 14 days. However, Lima et al (2015), with only one application of nitrogen fertilization, obtained seedlings with an average shoot height higher than those found in this study, which may be related to the fact that the authors used larger containers (3 dm 3 ), and according to Lisboa et al (2012), T. ciliata var. australis is very responsive to the volume of the container.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Similar to our work, Caldeira et al (2012) found out that higher shoot heights were obtained for substrates with a higher proportion of biosolids, which, among the substrates tested in their work, were also the one with the highest concentration of N. The shoot heights obtained with a higher proportion of biosolids were similar to those observed for seedlings submitted to a nitrogen concentration of 2000 mg L -1 for 7 days and 4000 mg L -1 for 14 days. However, Lima et al (2015), with only one application of nitrogen fertilization, obtained seedlings with an average shoot height higher than those found in this study, which may be related to the fact that the authors used larger containers (3 dm 3 ), and according to Lisboa et al (2012), T. ciliata var. australis is very responsive to the volume of the container.…”
Section: Discussioncontrasting
confidence: 80%
“…australis (Meliaceae family) presents a wood production with great economic value (BYGRAVE;BYGRAVE, 2005). Several studies have aimed to improve the seedling quality (MORETTI et al, 2011(MORETTI et al, , 2012CALDEIRA et al, 2012;LISBOA et al, 2012;SOMAVILLA et al, 2014;LIMA et al, 2015;MELO BRAGA et al, 2015), however, the production of T. ciliata var. australis seedlings still faces problems regarding the nutritional requirements, especially for nitrogen, which is one of the most required elements for its growth (MORETTI et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the leaf phosphorus level was directly proportional to the triple superphosphate doses (Figure 2j). Lima et al (2015) also reported that P doses are directly proportional to the levels thereof, in the shoot of Toona ciliata seedlings. Soares et al (2007) reported that the variation of 0-120 mg dm -3 of P 2 O 5 did not affect the phosphorus content in the shoot of soursop seedlings.…”
Section: Resultsmentioning
confidence: 91%
“…Isto porque, entre todos os tratamentos testados, não houve um destaque no desempenho das mudas inoculadas na comparação com as mudas não-inoculadas, independentemente da composição do substrato. A ausência do impacto positivo da inoculação com FMAs sobre mudas de espécies arbóreas pode ser devido à presença de elevadas concentrações de nutrientes, principalmente fósforo, que é promovida pela adubação dos substratos e diminui ou impede a colonização radicular por FMAs (Souza et al, 2009;Lima et al, 2015;Dalanhol et al, 2016). Acredita-se que esse resultado tenha ocorrido no presente estudo, em função de uma provável elevada disponibilidade de nutrientes no substrato promovida pela adição de esterco bovino de curral curtido.…”
Section: Discussionunclassified
“…Os FMAs promovem o incremento em altura, diâmetro e massa de matéria seca de mudas de espécies florestais produzidas em casa de vegetação (Lima et al, 2015). Esse fato é decorrente de benefícios nutricionais proporcionados pelos FMAs às plantas, com o aumento do volume de solo explorado pelo sistema radicular das plantas micorrizadas (Schiavo et al, 2009).…”
Section: Discussionunclassified